2010
DOI: 10.1021/jm9017543
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of a Novel Series of Semisynthetic Vancomycin Derivatives Effective against Vancomycin-Resistant Bacteria

Abstract: Novel semisynthetic vancomycin derivatives with antibacterial activity against vancomycin-resistant S. aureus (VRSA) were prepared. Replacement of Cl groups of vancomycin by Suzuki-Miyaura cross-coupling reaction, which gave the title compounds, is described for the first time. Introduction of a carbon substituent at the amino acid residue 2 of vancomycin led to an enhancement of antibacterial activity against vancomycin-resistant strains, whereas the additional introduction at the amino acid residue 6 resulte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
52
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(53 citation statements)
references
References 26 publications
1
52
0
Order By: Relevance
“…Molecular dynamic simulations and free energy calculations agree, favouring peptidoglycan-glycopeptide interactions rather than direct membrane binding of glycopeptides [16]. Surface plasmon resonance and other studies revealed a k d value for vancomycin binding of 1.32 μM [17], 2.7 μM [18] and 3.39 μM [19], indicative of moderate binding. In the case of the lipophilic glycopeptides such as teicoplanin which do not dimerise but do target the C-terminal D-Ala-D-Ala dipeptide of peptidoglycan [20], [21] with greater potency than vancomycin demonstrated in vitro and in vivo [22], [23], [24], anchorage into the membrane occurs via the lipid moiety and this anchorage positions the antibiotic at its site of action at the cell surface resulting in an increased effectiveness of the antibiotic [25], [26].…”
Section: Introductionmentioning
confidence: 58%
“…Molecular dynamic simulations and free energy calculations agree, favouring peptidoglycan-glycopeptide interactions rather than direct membrane binding of glycopeptides [16]. Surface plasmon resonance and other studies revealed a k d value for vancomycin binding of 1.32 μM [17], 2.7 μM [18] and 3.39 μM [19], indicative of moderate binding. In the case of the lipophilic glycopeptides such as teicoplanin which do not dimerise but do target the C-terminal D-Ala-D-Ala dipeptide of peptidoglycan [20], [21] with greater potency than vancomycin demonstrated in vitro and in vivo [22], [23], [24], anchorage into the membrane occurs via the lipid moiety and this anchorage positions the antibiotic at its site of action at the cell surface resulting in an increased effectiveness of the antibiotic [25], [26].…”
Section: Introductionmentioning
confidence: 58%
“…Vancomycin and related glycopeptide antibiotics inhibit the final steps of bacterial cell wall biosynthesis by binding to the C-terminal D-Ala–D-Ala peptide of the muramyl pentapeptide of peptidoglycan precursor Lipid II345678910. Surface plasmon resonance and other studies revealed values for the equilibrium dissociation constants (K d ) for vancomycin binding of 1.32 μM11, 2.7 μM12 and 3.39 μM13, indicative of moderate binding. Glycopeptide binding results in inhibition of transpeptidase and transglycosylase activities, affecting the crosslinking process in growing peptidoglycan, formation of glycan chains and incorporation of peptidoglycan precursors leading to osmotic shock and cell lysis141516.…”
mentioning
confidence: 99%
“…The emergence of vancomycin-resistant enterococci and Staphylococcus aureus is a serious concern in hospitals because vancomycin is the drug of choice for the treatment of nosocomial infections by methicillin-resistant S. aureus. Arimoto and co-workers [63] reported a novel methodology for the modification of vancomycin's carbon framework employing Suzuki-Miyaura cross-coupling reactions with the displacement of both chloro groups of residues at positions 2 and 6. Vancomycin·HCl (301) was reacted with a variety of phenylboronic acids in the presence of sodium 2-dicyclohexylphosphino-2 ,6 -dimethoxybiphenyl-3 -sulfonate (water extract of sweet potato leaves, WSPL) under MW irradiation affording analogs 302 in yields of up to 22%.…”
Section: Synthesis Of Analogs Of Natural Productsmentioning
confidence: 99%